The Introduction of Market Forces in the Public Hospital Sector : From New Public Sector Management to Organizational Reform - Jakab, Melitta; Preker, Alexander; Harding, April; Hawkins, Loraine (World Bank, Washington, DC, 2013)
This Discussion Paper was prepared as a background document for the Hospital Reform Module of the Joint Harvard/World Bank Institute Flagship Course on Health Sector Reform and Sustainable Financing. The Flagship course provides a practical review and update of current issues in health systems reform and financing for senior policy makers from developing countries. Since its inception, the Flagship course has reached more than 3,000 participants from over 50 countries. Heavy investment over the past 30 years has made the hospital sector the largest expenditure category of the health system in most developed and developing countries. Despite shifts in attention and emphasis toward primary care as a first point of contact for patients, in most countries, hospitals remain a critical link to health care, providing both advanced and basic care for the population. Often, they are the provider "of last resort" for the poor and critically ill. Although, it is clear that hospitals play a critical role in ensuring delivery of health services there is much less agreement about how to improve the efficiency and quality of care provided. This Discussion Paper provides insights into recent hospital reforms undertaken throughout the world, with an emphasis on organizational changes such as increased management autonomy, corporatization, and privatization. It provides some insights about these popular reform modalities from a review of the literature, reform experiences in other sectors and empirical evidence from hospital sector itself. The material presented tries to answer three questions: (a) what problems did this type of reform try to address; (b) what are the core elements of their design, implementation and evaluation; and, (c) is there any evidence that this type of reform is successful in addressing problems for which they were intended? While this paper focuses on issues related to the design of the reforms, the paper also reports the findings from a larger study that examined the implementation and evaluation of such reforms so that they will be available to countries that are considering venturing down this reform path.